Application of Business Continuity Planning to Monitoring Infrastructure for The Distribution of Social Assistance Funds at PT Bank BRI - Ayuni Widianti (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2026)
The distribution of social assistance funds is one of the important aspects in supporting the welfare of the community, especially in programs such as the Family Hope Program (PKH) and Basic Necessities. PT Bank Rakyat Indonesia (BRI) has a big responsibility in ensuring that the distribution of social assistance funds to beneficiaries is carried out on time, efficiently, and safely. In this context, the implementation of a Business Continuity Plan (BCP) in the monitoring infrastructure of the distribution of social assistance funds is very important, in order to maintain operational continuity despite unexpected disruptions or disasters. BCP focuses not only on operational recovery after an outage, but also on risk mitigation measures aimed at preventing disruptions from occurring. This article comprehensively discusses the application of BCP in the social assistance fund distribution monitoring system at PT Bank BRI, focusing on risk identification, the development of disaster recovery procedures, and the implementation of modern technology to support operational continuity. In addition, this article also explores the importance of regular simulations and testing in ensuring the readiness of systems and teams in dealing with emergency situations. This research aims to provide insight into how a structured BCP can strengthen the social fund distribution system and increase public trust in the management of social assistance. It is hoped that the results of this research can be a reference for other organizations that have similar responsibilities in managing the distribution of social assistance funds or other public services.